Occupational Determinants of Leptospirosis among Urban Service Workers - Azman Atil; Mohammad Saffree Jeffree; Syed Sharizman Syed Abdul Rahim; Mohd Rohaizat Hassan; Khamisah Awang Lukman; Kamruddin Ahmed (2020)
This study was carried out to determine the risk factors of leptospirosis infection among local urban service workers in Sabah. This is a cross-sectional study involving 394 workers in Kota Kinabalu City, Sabah, conducted from February to March 2017. Information on demography, occupational exposures and environmental factors was obtained by a modified validated questionnaire. Polymerase Chain Reaction (PCR) was used to determine the prevalence of positive leptospirae. The overall figure for positive leptospirae was 9.4% (95% CI: 6.8–12.8). Urban sweepers and lorry drivers made up the highest proportion of positive leptospirae respondents, contributing 15.5% and 9.4%, respectively. The significant risk factors for positive leptospirae were older age (p-value = 0.001), higher monthly salary (p-value = 0.039), longer duration of employment (p-value = 0.011) and working as an urban sweeper (p-value = 0.021). Leptospirae was prevalent among healthy urban service workers and relates to their working activities.